Cross-sectional Association Between Blood Pressure Status and Atrial Fibrillation in an Elderly Chinese Population. (20th April 2019) - Chen, Yi; Huang, Qi-Fang; Sheng, Chang-Sheng; Lei, Lei; Xu, Shao-Kun; Zhang, Wei; Shao, Shuai; Wang, Dian; Cheng, Yi-Bang; Wang, Ying; Guo, Qian-Hui; Zhang, Dong-Yan; et al.
Abstract: OBJECTIVE: Atrial fibrillation (AF) and hypertension are prevalent chronic disease conditions in the elderly population. In the present cross-sectional study, we investigated the association between blood pressure (BP) and AF in an elderly Chinese population. METHOD: Our elderly (≥65 years) subjects were residents recruited from 6 communities in Shanghai from 2006 to 2017. Atrial fibrillation was systematically screened by rest 12-lead electrocardiogram (ECG) or by a handheld single-lead ECG. BP status was defined according to the European hypertension guidelines as optimal, normal, or high-normal BP, and stage 1, 2, or 3 hypertension. RESULT: In the 6, 966 participants (women 56.0%, mean age: 72.3 years), the prevalence of AF was 3.3%, and the prevalence of hypertension was 58.7% (83.7% treated). In all participants, the association with prevalent AF was negative for systolic BP (odds ratio [OR] per 10-mm Hg increase 0.79, 95% confidence interval [CI]: 0.71–0.88, P < 0.0001) but positive for diastolic BP (OR per 5-mm Hg increase 1.11, 95% CI: 1.02–1.22, P = 0.02). In untreated participants ( n = 3, 544), the association with prevalent AF was U-shaped for both systolic and diastolic BP, with the nadir at high-normal BP and a significantly higher risk of prevalent AF in optimal systolic BP (OR: 3.11, 95% CI: 1.65–5.85, P = 0.004) and stage 2 or 3 diastolic hypertension relative to the nadir (OR: 8.04, 95% CI: 2.28–28.3, P = 0.001). CONCLUSION: In the elderly population, BP shows a complicated relationship with prevalent AF, with high-normal BP at the lowest risk and optimal systolic BP and stage 2 or 3 diastolic hypertension at increased risks.